Courthouse Rally Supporting Independent Supreme Court - Watkins, Howard::::::::: (1986)
Mary Louise Frampton and Daniel Olmos in front of "SUPPORT THE SUPREME COURT" banner Mary Louise wearing a Rose Bird YES button